Updating Knowledge of Drugs in Oral Implant Treatment - KISHIMOTO, Hiromitsu; HATTORI, Hirokazu; TAKAOKA, Kazuki (Journal of Japanese Society of Oral Implantology, 2023)
Patients desiring implant treatment often have systemic complications and use drugs. In order to stabilize implants over the long term, it is essential to have appropriate knowledge not only of drugs prescribed by dentists, but also of drugs prescribed by doctors, and constant updating of knowledge is required.As drugs prescribed by dentists, prophylactic administration of antibacterial agents should be given immediately before surgery for both tooth extraction and implant treatment；the use of amoxicillin is recommended in terms of antibacterial spectrum and bioavailability. As for analgesics, NSAIDs, which have many side effects such as renal damage, should be avoided；acetaminophen should be used.On the other hand, as drugs prescribed by doctors, in patients using direct oral anticoagulant (DOAC), there is no effective monitoring index such as PT-INR for warfarin, but adjusting the start time of surgery to account for the half-life can reduce the risk of bleeding. Implant surgery is not contraindicated in patients with osteoporosis who are using antiresorptive agents, but it is desirable to perform it after careful consideration of the risk of medication-related osteonecrosis of the jaw (MRONJ). Implant-associated MRONJ is often triggered by peri-implantitis rather than by implantation surgery, so careful consideration is required when planning implant treatment.